Are Rice Farming and Production in the Urban Farming Areas Still Efficient? A Stochastic Production Function Choice - Tamy Erissanti; Supadi Supadi; Suharno Suharno (Muhammadiyah University Press, 2021)
Lowland rice farming can still be found amidst the limited empty land in DKI Jakarta, especially the North Jakarta area. The alternative of increasing production that can be done in urban farming in limited land is increasing land efficiency. The novelty of this research is the analysis of the efficiency of farming carried out in the North Jakarta area because no one has discussed the research on efficiency in rice farming in North Jakarta. Thus, this research needs to determine the efficiency achieved by rice farmers and the factors that affect rice production in the North Jakarta area. The population in this study were all rice farmers producing in the North Jakarta area. This study’s sample was determined using the simple random sampling method with a total sample size of 80 respondents. The analytical method used in this research is the Stochastic Frontier Analysis (SFA) method. Based on the analysis, the average value of technical efficiency is 0.85, the value of allocative efficiency is 3.47, and the amount of economic efficiency is 2.95. The variables used to indicate that the variables of land area and fertilizer have a significant and positive effect. The variables of labor and education have a significant negative effect on rice production in North Jakarta; meanwhile, the variable of ownership right does not significantly affect rice production in North Jakarta.